The Principle of Non-Discrimination in Islamic Criminal Law: An Analysis of Qur’anic Verses on Theft - Muhammad Baihaqqi Assalimi; Agustiar; Ahmad Zikri (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2026)
This study examines the principle of non-discrimination in Islamic criminal law, specifically through a comprehensive analysis of the wording of Qur’anic verses related to the criminal act of theft (sariqah). The main issue of this study stems from the discourse regarding the simultaneous mention of male and female perpetrators, which is intended to represent equality; however, the grammatical structure of the verse prioritizes the mention of the male subject. Therefore, the central research question is whether this textual structure implies gender bias or, conversely, inherently affirms equality before the law. This study employs a qualitative method based on a literature review. Data analysis was conducted by integrating approaches from the sciences of tafsir, uṣūl al-fiqh, and maqāṣid al-syarī‘ah, and was further supported by an examination of empirical data. The results of the study indicate that the verse explicitly underscores the universality of binding criminal liability without distinguishing by gender, in line with the principle of equality before the law. As for the phrasing that prioritizes men, it must be understood contextually based on the empirical reality of perpetrator dominance, biological-psychological predispositions, and socio-economic responsibilities. Thus, the construction of this verse is not discriminatory but rather reflects substantive justice in Islamic law. Theoretically, this finding implies the importance of integrating a linguistic approach (naṣṣ) with sociological realities to refute gender-biased narratives. This study recommends a holistic contextual approach for legal scholars and practitioners in interpreting Sharia texts to avoid misconceptions of gender injustice.